Transformasi Paradigma Pembelajaran Akidah Akhlak dari Kurikulum 2013 ke Kurikulum Merdeka di MAN I Surakarta - Istikotimah Istikotimah; Joko Subando (Lembaga Yasin AlSys, 2026)
The transformation from the 2013 Curriculum to the Kurikulum Merdeka requires not only administrative changes but also changes in the learning paradigm and teachers’ mindset. Although the implementation of the Kurikulum Merdeka in Islamic Religious Education has been widely studied, research that specifically examines the transformation of Akidah Akhlak teachers’ mindset in the context of madrasah aliyah remains limited. This study aims to analyze the transformation of Akidah Akhlak teachers’ mindset in the transition from the 2013 Curriculum to the Kurikulum Merdeka at MAN 1 Surakarta. This study used a qualitative approach with a case study design. The research informants consisted of the Deputy Head of Madrasah for Curriculum and Akidah Akhlak teachers selected using purposive sampling. Data were collected through in-depth interviews, learning observations, and documentation study, then analyzed using the Miles, Huberman, and Saldaña interactive model through the stages of data condensation, data display, and conclusion drawing. The results showed that teachers’ mindset transformation occurred gradually, from a teacher-centered learning orientation toward student-centered learning. The main supporting factors for this transformation included curricular leadership, teacher learning communities, and Kurikulum Merdeka training, whereas inhibiting factors included deeply rooted teaching habits, limited time, and adaptation to learning documents. The conclusion of this study affirms that the successful implementation of the Kurikulum Merdeka is strongly influenced by changes in teachers’ paradigm and mindset. These findings imply the importance of strengthening curricular leadership, developing teacher learning communities, and providing continuous mentoring to support curriculum transition in madrasah aliyah.